Effect of altitude training on the aerobic capacity of athletes: A systematic review and meta-analysis - Chen, B.; Wu, Z.; Huang, X.; Li, Z.; Wu, Q.; Chen, Z. (Heliyon, 2023)
Purpose: With a growing number of athletes and coaches adopting altitude training, the impor tance for rationalizing and optimizing such training has been emphasized. We conducted a meta analysis to evaluate the influence of altitude training on athletes` aerobic capacity and to explore the best altitude training method to improve this capacity.